The Effect of Firm Size, Profitability, Solvency and Reputation of Public Accounting Firms on Audit Delay in LQ 45 Companies Listed on the Indonesia Stock Exchange in 2010-2016 - Karina Valisia Davis (International Journal of Applied Finance and Business Studies, 2020)
This study aims to analyze whether firm size, profitability, solvency and reputation of public accounting firm has an effect on audit delay at LQ 45 company listed on Indonesia Stock Exchange in 2010-2016. The measuring instrument used in this study is the total asset logarithm for firm size; return on assets (ROA) for profitability; debt to total asset ratio for solvency; and dummy variables for the reputation of the public accounting firm. The sampling method used in this research is purposive sampling and obtained data that passes the test as many as 18 companies sampled listed on index LQ 45 in Indonesia Stock Exchange in year 2010-2016 and 126 the number of observations. The data used is secondary data, namely the company's financial statements obtained from www.idx.co.id. Data collection techniques is by documentation techniques. The analysis used in this research is panel data regression analysis. The simultaneous test results show that all independent variables affect the dependent variable by 95 percent. Partial test results show that company size and solvency variables significantly affect audit delay, while the profitability and reputation of public accountant firm does not affect audit delay.